Control of amino acid transport into Chinese hamster ovary cells. Issue 12 (5th October 2018) - Geoghegan, Darren; Arnall, Claire; Hatton, Diane; Noble‐Longster, Joanne; Sellick, Christopher; Senussi, Tarik; James, David C.
Abstract: Amino acid transporters (AATs) represent a key interface between the cell and its environment, critical for all cellular processes: Energy generation, redox control, and synthesis of cell and product biomass. However, very little is known about the activity of different functional classes of AATs in Chinese hamster ovary (CHO) cells, how they support cell growth and productivity, and the potential for engineering their activity and/or the composition of amino acids in growth media to improve CHO cell performance in vitro. In this study, we have comparatively characterized AAT expression in untransfected and monoclonal antibody (MAb)‐producing CHO cells using transcriptome analysis by RNA‐seq, and mechanistically dissected AAT function using a variety of transporter‐specific chemical inhibitors, comparing their effect on cell proliferation, recombinant protein production, and amino acid transport. Of a possible 56 mammalian plasma membrane AATs, 16 AAT messenger RNAs (mRNAs) were relatively abundant across all CHO cell populations. Of these, a subset of nine AAT mRNAs were more abundant in CHO cells engineered to produce a recombinant MAb. Together, upregulated AATs provide additional supply of specific amino acids overrepresented in MAb biomass compared to CHO host cell biomass, enable transport of synthetic substrates for glutathione synthesis, facilitate transport of essential amino acids to maintain active protein synthesis, and provide amino acid substrates for coordinated antiport systems to maintain supplies of proteinogenic and essential amino acids. Abstract : Amino acid transporters (AATs) represent a key interface between the cell and its environment, critical for all cellular processes: Energy generation, redox control, and synthesis of cell and product biomass. However, very little is known about the activity of different functional classes of AATs in Chinese hamster ovary (CHO) cells, how they support cell growth and productivity, and the potential for engineering their activity and/or the composition of amino acids in growth media to improve CHO cell performance in vitro.